Enhancing social skills of children with autism spectrum disorder: The impact of differentiated learning in inclusive elementary schools - Lisdiana, Ana; Rochyadi, Endang; Sunardi, Sunardi; Rakhmat, Cece (UIN Raden Mas Said Surakarta, 2024)
This study investigates the implementation of the differentiated learning model as a strategy to enhance social skills in children with autism spectrum disorder (ASD). Adopting a qualitative approach with a descriptive method, data were gathered through observations, in-depth interviews, and document analysis at inclusive elementary schools in Bandung, Indonesia, that have incorporated differentiated learning models. The findings reveal that the application of the differentiated learning model involves key stages such as identifying students' needs, setting learning objectives, adjusting the curriculum, differentiating instruction, offering varied final product options, modifying the learning environment, and conducting continuous evaluations. These stages enable teachers to design learning activities tailored to the social and emotional needs of students with ASD. The study demonstrates that these adaptations significantly enhance the social skills of students with ASD in areas such as environmental care, attention-seeking, greeting others, maintaining a positive attitude, demonstrating responsibility, actively participating in learning, and engaging in group activities. The findings suggest that differentiated learning provides a structured and responsive approach to fostering social skills development in children with ASD, with potential implications for broader educational practices.